PROMOTING STUDENTS' READING COMPREHENSION WITH COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) - Halizatul Fhathah, Qary; ., Nuraeni (ENGLISH JOURNAL, 2020)
Cooperative Integrated Reading and Composition (CIRC) is one of cooperative learning method used in language teaching, specifically in high-level reading and writing. This method is designed to accommodate variety of student ability level with heterogeneous grouping or homogeneous grouping. CIRC aimed to develop students' ability in comprehending the content of reading and fostering the ability to write the materials they read. The purposes of this research were to know how CIRC is implemented in classroom, and to know to what extent CIRC promote students' reading comprehension. The researcher used classroom action research in conducting the research. The qualitative data was obtained from observation, interview, and documentation. The participants of the research were the 10th grade students of one senior high school in Bogor. The result of the research shows that CIRC can be implemented in two cycles and four meetings. The data shows that there are some competencies which indicates that CIRC promote students' reading comprehension in cognitive activity, motivation activity, and affective activity. This study suggests the good atmosphere and used another text to be implemented in other classes using CIRC.